Typhlocybella maidica (Hemiptera: Cicadellidae: Typhlocybinae: Dikraneurini), new species from Argentina - Catalano, María Inés; Paradell, Susana Liria; de Remes Lenicov, Ana María Marino (Zootaxa, 2009)
The tribe Dikraneurini, belonging to subfamily Typhlocybinae, is represented in the Afrotropical, Australian, Indomalayan, Nearctic, Neotropical and Paleartic regions with 201 genera and 31 subgenera recognized (Balme 2007). The genus Typhlocybella Baker, 1903 includes the following four species: Typhlocybella minima Baker, 1903 from Nicaragua, T. maculata Caldwell & Martorell, 1952 from Puerto Rico, T. parva Ruppel & DeLong, 1953 from Mexico and T. minuta (DeLong 1924) from Florida (USA) (Baker 1903, DeLong 1924, Caldwell & Martorell 1952, Ruppel & DeLong 1953). T. minima has been found on papaya, grasses, weeds, bushes, while T. maculata has been captured on grasses (Caldwell & Martorell 1952).